The challenges and opportunities for the development of COVID-19 therapeutics and preparing for the next pandemic - Ogbadoyi, Emmanuel O; Umar, Ndagi (Frontiers in Drug Discovery, 2022)
The disease which is today known as COVID-19 is caused by severe acute respiratory. Syndrome coronavirus 2 (SARS-COV-2), was first reported in Wuhan, China in December 2019. The disease has claimed well over six million lives from over 500 million cases. Vaccine hesitancy militates against successful mass vaccination. There is the rapid emergence of new SARS-COV-2 variants, constituting a challenge to the effectiveness of vaccines. Moreover, none of the available vaccines offers 100% protection and even the protection offered is of short duration necessitating booster doses to be taken. Moving forward, the development of plant-based edible vaccines will be a remarkable strategic approach to overcome vaccine hesitancy and improve vaccine uptake. So far only about nine drugs for COVID-19 treatment have approvals by either or both the European Medicines Agency and the FDA. While drug repurposing to address the emerging need in the early period of the COVID-19 pandemic has been contextually very useful, investment in it remains relatively low for commercial reasons arising from patenting issues. Embarking on new drug discovery and development strategies targeting both the virus and host factors is a very appealing option. Targeting druggable targets that are present across viruses, particularly the coronaviruses, for drug discovery and development represents an important strategy for pandemic preparedness. Natural products are an important reservoir of chemical scaffolds with huge potential for the discovery of novel chemical entities for development of novel therapeutics. Phytopharming is an available technology that can be used for mass and accelerated production of therapeutic molecules that will be required within short periods of time as is the case in pandemic outbreaks. Nanotechnology provides excellent platforms for formulating multivalent vaccines and pan-viral medicines for the treatment of COVID-19. Taken together, this review discusses the potential for the development of therapeutics by using the tools of biocomputing, nanotechnology, and phytopharming for accelerated therapeutic development to achieve effective COVID-19 treatment and associated complications, including new and emerging variants of SARS-COV-2 and other viral pandemics that may emerge or re-emerge.